Computational fluid and solid mechanics 2003 : proceedings, Second MIT Conference on Computational Fluid and Solid Mechanics, June 17-20, 2003 - Bathe, Klaus-Jurgen (Elsevier, 2003)
Papers presented at the biannual Conference containing information on the key challenges for research and development in computational mechanics, such as: the automatic solution of mathematical models, effective numerical schemes for fluid flows, the development of an effective mesh-free numerical solution method, the development of numerical procedures for multi-physics and multi-scale problems, the modeling of uncertainties, the analysis of complete life cycles of systems, and education.